Efficacy and Safety of Misoprostol Administered Rectally Compared with Oxytocin for the Prevention of Postpartum Hemorrhage - Shama Chaudhry; Hina Rajani; Rahima Rais; Habiba Sharaf Ali (ziauddin University, 2024)
Background: The foremost cause of maternal morbidity and mortality in third-world countries is Post-Partum Hemorrhage (PPH). To prevent PPH, often Misoprostol is used. This study aimed to find out the efficacy and safety profile of Misoprostol when administered rectally in comparison to oxytocin, to avoid the incidence of PPH. Methods: This quasi-experimental study on n=72 patients were performed at Ziauddin University and Hospital Karachi for 6 months (2021). The patients were divided into two groups. Oxytocin (10 IU) was administered intramuscularly to Group A(n=36) while 400ug of Misoprostol was given to group B(n=36) rectally, at the time of delivery. The level of hemoglobin was checked at the time of admission and 24 hours after delivery and side effects were also monitored. Chi-square and t-test were applied between both groups and a p-value <0.05 was taken as significant. Results: The average duration of the third stage of labor in the Misoprostol group was 5.3 minutes versus the Oxytocin (Syntocinon) group 3.75 minutes (p= 0.012). The decrease in the level of hemoglobin and the blood loss quantity was not significantly different in both groups (p=0.766, 0.203) respectively. The side effect of shivering was seen in group B in 4(11.1%) of the patients (p=0.04) and hyperthermia was observed in 2 (5.6%) (p=0.151). Conclusion: Misoprostol proved to be efficacious oxytocin in PPH prevention. Therefore, Misoprostol can likely be of help during the third stage of labor, especially in countries with developing healthcare setups. Keywords: Misoprostol; Postpartum Hemorrhage; Oxytocin; Maternal Mortality; Uterotonic.